Wild Native Chilli, Chile Piquin (Capscicum annuum L. var. aviculare Dierb.) in Northestern Mexico: Research Progress - Maiti, Ratikanta; Rodriguez, Humberto Gonzalez (International Journal of Economic Plants, 2017)
The paper gives a brief review on research progress on various aspects of Chile piquin (Capscicum annuum L. var. aviculare Dierb.), a native wild species of commercial importance in Northeast Mexico. It gives a background of the history of Chile piquin and its importance. Studies have been undertaken on morphology of the plant, its distribution in fields, root system, pollen viability. In addition, studies have been undertaken on pigment contents, water potential and biochemical composition of plant parts and fruits.